Newly Developed Neutralized pH Icodextrin Dialysis Fluid: Nonclinical Evaluation. Issue 8 (August 2016) - Yamaguchi, Naoya; Miyamoto, Keiichi; Murata, Tomohiro; Ishikawa, Eiji; Horiuchi, Takashi
Abstract: A two‐compartment system (NICOPELIQ; NICO, Terumo Co., Tokyo, Japan) has recently been developed to neutralize icodextrin peritoneal dialysis fluid (PDF). In this study, a nonclinical evaluation of NICO was carried out to evaluate biocompatibility as well as water transport ability. Glucose degradation products (GDPs) in the icodextrin PDFs were analyzed via high‐performance liquid chromatography (HPLC). The cell viability of human peritoneal mesothelial cells derived from peritoneal dialysis effluent (PDE‐HPMCs) was evaluated as well as the amount of lactate dehydrogenase (LDH) released after exposure to different PDFs (NICO and EXTRANEAL [EX, Baxter Healthcare Corp., Chicago, IL, USA]) and neutralized pH glucose PDF MIDPELIQ 250 (M250, Terumo). The water transport ability of NICO, EX, and M250 was tested using dialysis tube membranes with various pore sizes: 1, 2, 6–8, and 12–16 kDa. Although cell viability decreased by 30% after 30 min exposure to NICO, it was maintained for 6 h while a significant decrease was observed after 6 h exposure to EX. However, following adjustment of the pH to the same pre‐exposure pH value, there was no significant difference in cell viability within the same pH group despite a doubling of the difference in the total amount of GDPs (44.6 ± 8.6 µM in NICO and 91.9 ± 9.5 µM in EX, respectively). In contrast, a significant decrease in cell viability was observed when the pH decreased to less than pH 6. Levels of released LDH, a cytotoxic marker, were within 5% after a 6‐h exposure of NICO to PDE‐HPMCs. There was no significant difference in water transport ability represented as overall osmotic gradients between NICO and EX. In conclusion, neutralization of icodextrin PDF is beneficial for maintaining cell viability and minimizing LDH release while water transport ability is comparable to the conventional icodextrin PDF.